Quinoline conjugated 2-azetidinone derivatives as prospective anti-breast cancer agents: In vitro antiproliferative and anti-EGFR activities, molecular docking and in-silico drug likeliness studies - K. Govindarao; N. Srinivasan; R. Suresh; R.K. Raheja; Sivakumar Annadurai; Richie R. Bhandare; Afzal B. Shaik (Journal of Saudi Chemical Society)
Two series [1–8 (series-1) and 9–16 (series-2)] of quinoline conjugated 2-azetidinones were evaluated for their antiproliferative potential against breast cancer cell lines MCF7 and MDA-MB-231 respectively. All the compounds were more active towards against MCF7 than MDA-MB-231 cancer cell lines and few compounds activity was more than the standard erlotinib. For instance, the compound 16 of series-2 bearing electron withdrawing fluorine atom at the 6th position of quinoline ring showed promising activity with MIC values of 2.33 ± 0.19 µg/mL for MCF7 and 4.19 ± 0.22 µg/mL for MDA-MB-231 cells, respectively. In a similar way, the compounds 8 and 14 containing fluorine and chlorine substituents respectively, and located at position-6 of quinoline scaffold showed better activity than erlotinib. The ability of target compounds to inhibit EGFR tyrosine kinase, one of the key enzymes involved in breast carcinomas was evaluated by in vitro enzymatic assay and it was found that the compound 8 had close inhibitory activity to erlotinib with an %inhibition of 97.1 ± 0.08 at 10 µM. The compounds showed selective toxicity on the cancer cell lines as their IC50 values are high against the human normal liver cell line-LO2. Further, the docking studies of the promising compounds 8, 14 and 16 revealed the important molecular interactions with the EGFR kinase enzyme (PDB ID: 6S9B). The physicochemical and pharmacokinetic properties of the most active compounds were predicted using Swiss ADME and pkCSM tools respectively. The most promising compounds arisen from the present study can be considered as prospective lead molecules for anticancer activity against breast carcinoma.